PENGARUH LATIHAN MENENDANG LIMA BOLA KE GAWANG TERHADAP AKURASI SHOOTING PADA TIM SEPAK BOLA KOTO RANAH - Reflis '; Ramadi '; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem with this research it`s still a lack of accuracy shooting at the time of exercise as well as compete on the football team Koto Ranah. Based on the researchers training provide kick him in five balls to the goal to improve the accuracy of the shooting. The research to determine whether there is effect kick him in five the ball into the net on the accuracy of the shooting on the football team Koto Ranah, so that when a shooting get maximum results. The research is experimental treatment (Experimental), with a population football team Koto Ranah, the data in this research is the entire population of 16 people. The instruments used in this research is to test Johnson soccer tes, which aims to tes menembak bola ke sasaran. It aims tomeasure the ability and skills to shoot the ball into the target (shooting), normality test with lilifors test at significance level α (0.05). The hypothesis is the effect kick him in five the ball into the net on the accuracy of the shooting. Based on the analysis of statistical data, there are an average Pree-test of 56,21 and an average post-test 63,47, then the data is normal with an increase of 7,26. Based on t test analysis produces Ttabel Thitung of 6,78 and 1,753, meaning Thitung> Ttabel. Thus, there Effect of Exercise kick him in five the ball into the net on the accuracy of the shooting on the football team Koto Ranah.Keywords : Kick Him In Five The Ball Into The Net, Accurasi Shooting.